2005
DOI: 10.2460/javma.2005.226.232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surgical technique on limb function after surgery for rupture of the cranial cruciate ligament in dogs

Abstract: Surgical technique can influence limb function after surgery. Labrador Retrievers treated via LSS, ICS, or TPLO for repair for of RCCL and medial meniscal injury managed with partial or complete meniscectomy infrequently achieve normal function. Results of LSS and TPLO are similar and superior to ICS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
304
1
22

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(345 citation statements)
references
References 13 publications
18
304
1
22
Order By: Relevance
“…A cirurgia é recomendada para todos os cães, pois acelera a taxa de recuperação e potencializa a função (SCHWARZ, 2003). CONZEMIUS et al (2005) observaram que, em cães de raças grandes, a sutura extracapsular de estabilização lateral e a osteotomia niveladora do platô tibial (TPLO) apresentaram resultados similares e superiores à estabilização intra-articular "over-the-top". Para CHAUVET et al (1996), quando a facilidade do procedimento e a satisfação do cliente são os objetivos do cirurgião, parece que a sutura fabelo-tibial é a melhor opção para cães grandes com RLCC; quando a meta é o pleno retorno da função e a prevenção da doença articular degenerativa, nenhum procedimento cirúrgico é satisfatório.…”
Section: Introductionunclassified
“…A cirurgia é recomendada para todos os cães, pois acelera a taxa de recuperação e potencializa a função (SCHWARZ, 2003). CONZEMIUS et al (2005) observaram que, em cães de raças grandes, a sutura extracapsular de estabilização lateral e a osteotomia niveladora do platô tibial (TPLO) apresentaram resultados similares e superiores à estabilização intra-articular "over-the-top". Para CHAUVET et al (1996), quando a facilidade do procedimento e a satisfação do cliente são os objetivos do cirurgião, parece que a sutura fabelo-tibial é a melhor opção para cães grandes com RLCC; quando a meta é o pleno retorno da função e a prevenção da doença articular degenerativa, nenhum procedimento cirúrgico é satisfatório.…”
Section: Introductionunclassified
“…The development of surgical procedures that promote changes in joint anatomy and biomechanics constitutes a new perspective to decrease osteoarthrosis progression and restore normal limb function (MONTAVON et al, 2002). The Tibial Plateau Leveling Osteotomy (TPLO) has been studied and used worldwide, especially in the United States and Europe, with promising results (WARZEE et al, 2001;BALLAGAS et al, 2004;CONZEMIUS et al, 2005). Although cranial drawer movement is not eliminated, TPLO leads to the functional stability of the stifle joint during the stance phase of locomotion (REIF et al, 2002;BALLAGAS et al, 2004).…”
mentioning
confidence: 99%
“…Although cranial drawer movement is not eliminated, TPLO leads to the functional stability of the stifle joint during the stance phase of locomotion (REIF et al, 2002;BALLAGAS et al, 2004). Despite the overall acceptance by most surgeons, studies using force plate analysis showed similar results in long-term outcome from the lateral suture technique and the Slocum TPLO (BALLAGAS et al, 2004;CONZEMIUS et al, 2005).…”
mentioning
confidence: 99%
“…There was never any real study of the old techniques and their advantages and disadvantages before the proposed change to osteotomy techniques first by Barclay Slocum in 1994 was accepted, and there still is none in spite of wide acceptance of these new and much more radical techniques [1] compared the TPLO to the lateral suture technique [2]. Did some radiographic comparisons of outcomes between TPLO and lateral suture.…”
Section: Introductionmentioning
confidence: 99%